2018
DOI: 10.1146/annurev-neuro-080317-062155
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Plasticity of Neurotransmitter Release: Emerging Mechanisms and Contributions to Brain Function and Disease

Abstract: Long-lasting changes of brain function in response to experience rely on diverse forms of activity-dependent synaptic plasticity. Chief among them are long-term potentiation and long-term depression of neurotransmitter release, which are widely expressed by excitatory and inhibitory synapses throughout the central nervous system and can dynamically regulate information flow in neural circuits. This review article explores recent advances in presynaptic long-term plasticity mechanisms and contributions to circu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
113
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(123 citation statements)
references
References 180 publications
(222 reference statements)
1
113
0
1
Order By: Relevance
“…Presynaptic mitochondria can modulate short-term plasticity of neurotransmitter release via their sequestration and slow release of calcium (Billups and Forsythe, 2002;Sun et al, 2013;Kwon et al, 2016). Also, presynaptic release probability does correlate with overall synaptic strength and vesicle pool size suggesting that there may be a link between mitochondrial influence on presynaptic release and the likelihood of a synapse becoming stronger and/or more stable (Monday et al, 2018). However, it remains unknown whether mitochondria directly influence long-term plasticity of synaptic function, as recently shown within dendrites (Smith et al, 2016;Divakaruni et al, 2018), or are simply recruited by alterations in synaptic activity to support ongoing presynaptic function (Vaccaro et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Presynaptic mitochondria can modulate short-term plasticity of neurotransmitter release via their sequestration and slow release of calcium (Billups and Forsythe, 2002;Sun et al, 2013;Kwon et al, 2016). Also, presynaptic release probability does correlate with overall synaptic strength and vesicle pool size suggesting that there may be a link between mitochondrial influence on presynaptic release and the likelihood of a synapse becoming stronger and/or more stable (Monday et al, 2018). However, it remains unknown whether mitochondria directly influence long-term plasticity of synaptic function, as recently shown within dendrites (Smith et al, 2016;Divakaruni et al, 2018), or are simply recruited by alterations in synaptic activity to support ongoing presynaptic function (Vaccaro et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…It is now well-established that Hebbian plasticity resembles fast and lasting input-specific synaptic changes necessary for experience-dependent memory and learning (Bear, 1996;Chen and Tonegawa, 1997;Klintsova and Greenough, 1999). Experimentally, Hebbian mechanisms have been described in detail for excitatory pre-and postsynaptic sites (e.g., Petzoldt et al, 2016;Monday et al, 2018;Scheefhals and MacGillavry, 2018;Buonarati et al, 2019), where, for example, tetanic electrical stimulation at different frequencies results in the strengthening (long-term potentiation, LTP) or weakening (long-term depression, LTD) of neurotransmission (Bliss and Lomo, 1973;Dudek and Bear, 1992). Meanwhile, evidence has started to emerge for corresponding activity-dependent synaptic changes at GABAergic synapses (Bartos et al, 2011;Rozov et al, 2017;Chiu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Recent data suggest that memory precision defects can be generated by deregulation of genes involved in hippocampus Dentate Gyrus-CA3 connections, in particular Dentate Gyrus Mossy Fibers (MF)-CA3 synapse (18,(34)(35)(36)(37)(38). A During contextual fear memory consolidation, the strength of mossy fiber connections is selectively increased between dentate gyrus engram cells and CA3 engram cells (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, using in situ hybridization, we found that deregulation of DYRK1A dosage indirectly induced changes in expression of genes encoding pre-synaptic proteins. Altogether, these results prompted us to investigate whether the synaptic plasticity is impaired in the Dentate Gyrus Mossy Fiber-CA3 pathway that is known to involve a presynaptic form of LTP linked to presynaptic proteins (17,18). Therefore, using extracellular field recording in hippocampal slices, we found that the NMDA-independent long-term potentiation of the Dentate Gyrus-CA3 synapses is specifically impaired in these two mouse lines.…”
Section: Introductionmentioning
confidence: 94%